2014
DOI: 10.3855/jidc.3766
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and antibiotic susceptibility patterns of urinary pathogens in male outpatients in Argentina

Abstract: Introduction: Knowledge of the etiology and antimicrobial susceptibility patterns of uropathogens is important for determining the best treatment option. This study aimed to determine the distribution and antibiotic susceptibility patterns of bacterial strains isolated from adult male outpatients. Methodology: Between November 2012 and April 2013, 3,105 community urine samples were analyzed from adult male patients who attended the Laboratorio Hidalgo, Buenos Aires, Argentina. Antimicrobial susceptibility test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
3
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
7
3
2
2
Order By: Relevance
“…According to our results, not one agent could be declared fit for empiric use in elderly patients. Our findings are in accordance with numerous studies which also encountered high resistance rates among older age groups [24][25][26][27].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…According to our results, not one agent could be declared fit for empiric use in elderly patients. Our findings are in accordance with numerous studies which also encountered high resistance rates among older age groups [24][25][26][27].…”
Section: Discussionsupporting
confidence: 82%
“…Guidelines state that if resistance to an antimicrobial agent exceeds the 20% threshold, it should no longer be recommended for empiric therapy [5,13,23]. Resistance rates among different age groups were observed to increase as the age of the patient increased, which supports claims from other studies [24][25][26][27]. Pathogens isolated from patients within the age group 18-34 years showed low rates of resistance to several antimicrobial agents (<10%), most notably to amikacin (4.2%), ceftriaxone (7.7%), cefepime (8.0%), and norfloxacin (10.0%), which implies that these agents should be used as firstline therapy for this age group in our population.…”
Section: Discussionsupporting
confidence: 78%
“…Our findings for the fosfomycin MIC against E. coli and Klebsiella spp. were consistent with those reported in recent studies that evaluated in vitro susceptibility profiles (1,19,20). Fosfomycin presented high levels of activity against E. coli.…”
Section: Discussionsupporting
confidence: 81%
“…Susceptibility to amikacin in our study was high as it was in studies carried out in other parts of the world [ 43 , 46 , 47 ]. However, the resistance to tetracycline in our study was 50% while in another study it was reported to be 26% [ 48 ].…”
Section: Discussionsupporting
confidence: 46%
“…No resistance to vancomycin, imipenem and doxycycline was observed among the studied isolates. In previous studies a high sensitivity to imipenem has been also reported [ 43 – 46 ]. These antibiotics seems to be a good choice for the treatment of UTI caused by E. coli but it should be considered that unlimited use of these antibiotics can gradually lead to increasing antibiotic resistant.…”
Section: Discussionmentioning
confidence: 67%